Optimizing Electrode Performance in EMG and EIT for Superior Muscle Data Acquisition - Melchor Uceda, Irán Arane; Gutiérrez Gnecchi, José Antonio; González Vázquez, Alberto; Reyes Archundia, Enrique; Olivares Rojas, Juan Carlos; Méndez Patiño, Arturo; Robledo Ayala, Alejandro Israel (Revista Mexicana de Ingenieria Biomedica, 2025)
Optimizing electrode performance in electromyography (EMG) and electrical impedance tomography (EIT) is critical to advancing muscle data acquisition. This study systematically evaluates various electrode types, shapes, and materials, focusing on optimizing signal-to-noise ratio, durability, and long-term usability. A key contribution of this research is the identification of stainless-steel electrodes as the most efficient option, demonstrating superior signal stability, oxidation resistance, and reusability compared to disposable alternatives. This finding not only improves the reliability of EMG and EIT measurements but also offers a sustainable and cost-effective solution for clinical and research applications. By providing empirical evidence on electrode selection and design, this study lays the foundation for improved methodologies in rehabilitation, sports medicine, and neurology, ultimately improving patient care and deepening understanding of muscle physiology.